The Ritual Use of Jhakro in Magar Community - Sapkota, Prakash Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2011)
Human- plant relation is tightly attached on life of human beings. From the beginning of civilization, people used many plants and their products for different purpose to adopt with their environment. The essential and valuable materials including plant species are gathered, used, saved and always remain hunger for knowledge yet now. They developed different kinds of ceremonies and rituals and include valuable materials and plants within it to protect and remains as indigenous knowledge in particular communities and groups. In this context, I want to raise the issue of material culture to search why people used plants in their rituals with reference to a plant species the Jhakro the Magars inhabitant of Baglung district, western Nepal. The research was carried out by using descriptive and exploratory research design. Observation, interview and group discussion were used in the field for primary data collection. The Magars are rich in their rituals among them death and kul pujane rituals are significant for cohesive and solidarity of the group; within these rituals a shrub plant species with special type of smell remains in central position for purity and soul. They believed that in death ritual all the polluted activities are purified and in kul pujane Jhakro acts as purity as well as help to join their ancestors with them. Unfortunately, they are unknown of the materialistic meaning of it due to lack of transferring knowledge. In etic aspect, this plant has important medicinal properties and the Magar preserved by keeping it in important rituals within their community. Keywords: Ritual; Jhakro; the Magars; ethno-botany; ancestors DOI: 10.3126/dsaj.v4i0.4522 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.223-234